(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the issues of the accuracy of medical terms. An analysis of scientific literature on this branch of knowledge shows that its terminology needs a certain streamlining and unification.